Experiences of registered and student nurses regarding the clinical supervision in medical and surgical wards: Develop an educational programme to support registered nurses - Neshuku, Hanna; Amukugo, Hans Justus (International Journal of Medicine, 2015)
The purpose of the study was to explore and describe the lived experiences of registered nurses and student nurses regarding the clinical supervision of student nurses in medical and surgical wards. The findings will be a basis to develop an educational programme to support registered nurses during clinical supervision in the same context.The study was a qualitative, explorative, descriptive and contextual in nature. This paper describes Phase 1, of the study aimed to explore and describe the experiences of registered nurses and student nurses regarding clinical supervision of student nurses. Data was collected through in-depth individual face to face interviews thereafter data were analysed based on the Tesch’s method of qualitative data analysis. The numbers of interviews conducted were 35 in total, made up of 27 interviews with student nurses and 8 interviews with registered nurses. The numbers were determined based on the subject who availed themselves for the study as well as data saturation.Study revealed managerial, educational as well as non-conducive environment challenges experiences by registered nurses and student nurses during clinical supervision of student nurses.It was concluded that educational programme should be developed in order to support registered to manage those challenges. The development of the programme is outlined in article part 2.